Production of two SARS-CoV-2 neutralizing antibodies with different potencies in Nicotiana benthamiana - Frigerio, Rachele; Marusic, Carla; Villani, Maria Elena; Lico, Chiara; Capodicasa, Cristina; Andreano, Emanuele; Paciello, Ida; Rappuoli, Rino; Salzano, Anna Maria; Scaloni, Andrea; Baschieri, Selene; Donini, Marcello (Frontiers in Plant Science, 2022)
Monoclonal antibodies are considered highly effective therapeutic tools for the treatment of mild to moderate COVID-19 patients. In the present work, we describe the production in plant of two SARS-CoV-2 human IgG1 monoclonal antibodies recognizing the spike protein receptor-binding domain (RBD) and endowed with neutralizing activity (nAbs). The first one, mAbJ08-MUT, was previously isolated from a COVID-19 convalescent patient and Fc-engineered to prolong half-life and reduce the risk of antibody-dependent enhancement. This nAb produced in mammalian cells, delivered in a single intramuscular administration during a Phase I clinical study, was shown to: i) be safe and to effectively protect against major variants of concern; ii) have some neutralizing activity against the recently emerged omicron variant in a cytopathic-effect-based microneutralization assay (100% inhibitory concentration, IC100 of 15 g/mL). The second antibody, mAb675, previously isolated from a vaccinated individual, showed an intermediate neutralization activity against SARS-CoV-2 variants. Different accumulation levels of mAbJ08-MUT and mAb675 were observed after transient agroinfiltration in Nicotiana benthamiana plants knocked-out for xylosil and fucosil transferases, leading to yields of 35 and 150 mg/kg of fresh leaf mass, respectively. After purification, as result of proteolytic events affecting the hinge-CH2 region, a higher degradation of mAb675 was observed, compared to mAbJ08-MUT (18% versus 1%, respectively). Both nAbs showed a human-like glycosylation profile, and were able to specifically bind to RBD and to compete with angiotensin-converting enzyme 2 binding in vitro. SARS-CoV-2 neutralization assay against the original virus isolated in Wuhan demonstrated the high neutralization potency of the plant-produced mAbJ08-MUT, with levels (IC100 ∼17 ng/mL) comparable to those of the cognate antibody produced in a Chinese hamster ovary cell line; conversely, mAb675 exhibited a medium neutralization potency (IC100  200 ng/mL). All these data confirm that plant expression platforms may represent a convenient and rapid production system of potent nAbs to be used both in therapy and diagnostics in pandemic emergencies.